Mild Cleavage of N–O Bond of 3,6-Dihydro-1,2-oxazines by Condensation of Aldehydes in Aqueous Media - Galvani, Gilles; Lett, Robert; Kouklovsky, Cyrille (Synlett, 2015)
The nonreductive cleavage of a model 3,6-dihydro-1,2-oxazine by condensation of 2,2-dimethoxyacetaldehyde under aqueous conditions is investigated. Depending on the pH of the solution, the reaction leads either to the N-acylated 1,4-amino alcohol or to the corresponding stable hemiaminal. The formation of the former is believed to proceed through iminium to oxaziridine rearrangement and not through enamine formation, as confirmed by the use of nonenolizable aldehydes. This procedure allows a very mild, nonreductive cleavage of N–O bonds.
Keywords: nitrogen; imines; ring opening; aldehydes; heterocycles